The problem of the formation of the complete image of object - Lapė, J. (Psichologija, 1963)
The article briefly discusses the main ways of solution of the problem of complete image formation of an object and analyzes the newest studies of Soviet psychologists on this matter. The ideas of the representatives of the Association and Gestalt are discussed. More attention is paid to the works of Soviet psychologists I. Pavlov, I. Sechenov, B. Ananjev, A. Leontjev, and others.
Keywords: perception; perception of object; complete perception of objects